The Development of Basic Arabic E-Module Using Fliphtml5 as Alternative Teaching Material - Amin, Nur Fadilah; Tadjuddin, Andi Fajriwati; Nasruni, Nasruni; Hidayah, Nurul (Universitas Islam Negeri Raden Intan Lampung, 2022)
To improve learning activities in the Arabic course for students of Universitas Muhammadiyah Makassar in this pandemic period, digital teaching materials are needed. The development of the basic Arabic language in this university is important because Arabic is one the courses taught in almost every study program. The method that was used to develop this electronic module is the 4D method which consists of the Define, Design, Develop, and Disseminate stage. The data sources in this development are divided into two parts. The first data sources relating to the development of books are taken from Arabic books while the data sources used as test subjects are 43 students of the Islamic Economics Study Program, Faculty of Economics and Business, Universitas Muhammadiyah Makassar. The results of this development were an electronic module using Fliphtml5 as a development design template while the method of presenting material in this E-Module follows the model of the Directorate general of Islamic religious institution and open university modules in 1996. Which begins with an introduction, and contains learning activities, exercises and summeries. The percentage of the respondents reached 92% and 96% which explains to us that the material of the Arabic E-Module is easier to understand as an alternative teaching materials for this course. Then as a conclusion of the result, this E-Module can be used as teaching materials to improve Arabic learning activities.